"TAMING THE ELEPHANT IN THE (CLASS)ROOM: EXPLORING ROOT CAUSES OF STUDENT BOREDOM". Issue 4 (2nd October 2019) - Dugan, Riley; Zhang, Chun; Kellaris, James; Sweeney, Ric
Abstract : Despite being a pervasive emotion that is felt across occupational and educational contexts, boredom has heretofore been underexplored in the marketing education literature. This research attempts to rectify this notable omission by presenting two studies that lend insight into the individual personality characteristics that make students particularly prone to feelings of boredom. Through the theoretical lenses of the 3M hierarchical model of personality and Control-Value theory, Study 1 provides evidence that trait neuroticism, conscientiousness and need for arousal operate through impulsivity to shape marketing students' feelings of boredom in the classroom, but that this effect is attenuated when students are high in self-efficacy. In Study 2, we conduct an experiment that provides converging evidence of the role of self-efficacy in attenuating these perceptions. Finally, we discuss what marketing educators can do to alleviate perceptions of a boring classroom, and discuss avenues for future research.